Hubungan Disiplin Belajar dengan Prestasi Belajar pada Siswa Kelas VIII - Sintia Setiawati; Ifani Candra; Harry Theozard Fikri (Psyche 165 Journal, 2020)
The research aims to knowing relationship between learning discipline and learning achievement in VIII grade student junior high school. Independent variables in this study is learning discipline and dependent variables is learning achievement. This measuring instrument used in this study is the scale of learning discipline. Sampling technique in this study use random sampling technique. The sample in this study was 110 VIII grade student. For Y variable (learning achievement) data using semester 1 and 2 average values. Learning discipline questioner before being used for research try it first. Validity and reliability tes in this study using alpha cronbach technique. The result of the trials of the two instrument are only valid questioner which will be used in the research. The result of the coefficients on the learning discipline move from rix=0,348 to rix= 0,685 with a reliability coefficients of α = 0,867. Based on data analysis, obtained a correlation value of 0,226 with significant level of 0,018<0,05 whichmean hypothesis is accepted. The show that there is weak and unidirectional relationship between learning achievement in class VIII in junior high school 1 in solok city that is, if the higher learningdiscipline ,the higher learning achievement. As for the effective contribution of the learning discipline of learning achievement of 5%